Caries experience and risk indicators of having decayed teeth among 65-year-olds in Oslo, Norway: a cross-sectional study - My Tien Diep; Rasa Skudutyte-Rysstad; Anne Thea Tveit Sødal; Alix Young; Lene Hystad Hove (BMC, 2023)
Abstract Background Meeting the oral health needs of the increasing population of older adults presents a major challenge in dental care. Knowledge about the oral health status in the young-elderly age group is essential for the planning of future oral health education and prevention programs. The aims of the present study were therefore to investigate the caries experience among 65-year-olds in Oslo, Norway, and to explore associations between having decayed teeth and sociodemographic, behavioural, and biological factors. Methods A random sample of 65‑year‑olds in Oslo answered a questionnaire and underwent clinical and radiographic examinations (n = 457, 52% men and 48% women) at the Research Clinic, Faculty of Dentistry, University of Oslo, between February and December 2019. Primary- and secondary coronal and root caries lesions, root remnants, and missing and restored teeth were recorded. Decayed teeth (DT) were defined as teeth with coronal- and root caries lesions that had progressed into dentine and root remnants, and the DMFT/S scores were calculated. Results The mean number of teeth was 25 (SD: 4) and the mean DMFT was 19.4 (SD: 4.7). Thirty seven percent of the individuals had at least one decayed tooth (DT > 0), and the mean number of filled teeth (FT) was 16.1 (SD: 5.4). Multivariable logistic regression analysis showed that male gender (OR: 1.8, 95% CI: 1.2-2.8), basic level of education (OR: 1.9, 95% CI: 1.2-2.9), irregular dental attendance (OR: 2.2, 95% CI: 1.0-4.8), and hyposalivation (OR: 2.1, 95% CI: 1.0-4.4) were significant risk indicators for having decayed teeth (DT > 0) (p < 0.05). Conclusions In conclusion, 65-year-olds in Oslo had a low average number of decayed and missing teeth, and a high number of restored teeth. Irregular dental attendance and hyposalivation were the strongest risk indicators for having decayed teeth. Based on the present results, it will be important to ensure access to regular dental care and to increase the emphasis on caries preventive measures for individuals with hyposalivation in this age group.